Pengaruh Pandemi Covid-19 dalam Proses Pembelajaran BIPA di Universitas Negeri Surabaya - Abrian, Rizky Abrian; Sulistiawati, Afwin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study examines how the impact of the emergence of the Covid-19 Pandemic on the BIPA (Bahasa Indonesia Penutur Asing) learning process at the State University of Surabaya. The formulation of the problem in this study is (1) How is the influence of the Covid-19 pandemic on the learning conditions of BIPA at the State University of Surabaya? (2) How are the efforts of the State University of Surabaya in overcoming obstacles in BIPA learning due to the Covid-19 pandemic? The method used in this research is to conduct interviews by conducting a survey of BIPA teachers and stakeholders in State University of Surabaya especially BIPA program. The results obtained, there are new problems from the Covid-19 pandemic, limited mobility, and activities in the learning process, plus students who cannot come to the country where they study. On the other hand, the university is looking for a solution by adjusting the learning process using an innovative online learning process to deal with students who cannot come to Indonesia due to the Covid-19 pandemic.